Calculation of Maximum Water Content in Various Natural Gases by Using Modified Peng-Robinson Equation of State - Rajzinger, Jan (Communications - Scientific letters of the University of Zilina, 2012)
During the expansion of natural gas in the pipeline, the gas cools down due to the Joule-Thomson effect and due to the interaction between pipeline system and its surroundings to the conditions at which gas is saturated by water vapors, and gas is not able to keep excess humidity and its condensation and hydrate formation will occur. For that reason it is necessary to identify the critical parts of the pipeline systems, maximum water content in the gas, to choose appropriate physical model, and apply appropriate solutions which also will considerably influence energy consumption requirements. For the physical model development, method based on equality of fugacity concept with modified Peng-Robinson equation of state and Rachford-Rice appropriate solution algorithm are used to develop the model estimating the water content in equilibrium with natural gas. The results of the presented method are compared with selected experimental data from the literature.